The Human Factor: Student Reactions to the Integration of Personal Dispositions Into a Counseling Program. Issue 1 (7th April 2013) - GIBBONS, MELINDA M.; COCHRAN, JEFF L.; SPURGEON, SHAWN; DIAMBRA, JOEL F.
Abstract : The authors explored student reactions to the integration of personal dispositions, or characteristic attitudes, into a counseling program. Results suggested participants liked focusing on personal dispositions and were able to identify areas of personal growth related to these characteristics. Integrating humanistic principles by using dispositions is recommended when training future counselors.